A mediator-based approach to ontology generation and querying of molecular and phenotypic cereals data. (2nd June 2009) - Sala, Antonio; Bergamaschi, Sonia
We describe the development of the CEREALAB ontology, an ontology of molecular and phenotypic cereals data, that allows identifying the correlation between the phenotype of a plant with its molecular data. It is realised by integrating public web databases with the database developed by the research group of the CEREALAB laboratory. Integration is obtained semi-automatically by using the Mediator envirOnment for Multiple Information Sources (MOMIS) system, a data integration system developed by the Database Group of the University of Modena and Reggio Emilia, and allows querying the integrated data sources regardless of the specific languages of the source databases.